Update on transcobalamin deficiency: clinical presentation, treatment and outcome. Issue 3 (5th December 2013) - Trakadis, Y. J.; Alfares, A.; Bodamer, O. A.; Buyukavci, M.; Christodoulou, J.; Connor, P.; Glamuzina, E.; Gonzalez‐Fernandez, F.; Bibi, H.; Echenne, B.; Manoli, I.; Mitchell, J.; et al.
Abstract: Transcobalamin (TC) transports cobalamin from blood into cells. TC deficiency is a rare autosomal recessive disorder usually presenting in early infancy with failure to thrive, weakness, diarrhoea, pallor, anemia, and pancytopenia or agammaglobulinemia. It can sometimes resemble neonatal leukemia or severe combined immunodeficiency disease. Diagnosis of TC deficiency is suspected based on megaloblastic anemia, elevation of total plasma homocysteine, and blood or urine methylmalonic acid. It is confirmed by studying the synthesis of TC in cultured fibroblasts, or by molecular analysis of the TCN2 gene. TC deficiency is treatable with supplemental cobalamin, but the optimal type, route and frequency of cobalamin administration and long term patient outcomes are unknown. Here we present a series of 30 patients with TC deficiency, including an update on multiple previously published patients, in order to evaluate the different treatment strategies and provide information about long term outcome. Based on the data presented, current practice appears to favour treatment of individuals with TC deficiency by intramuscular injections of hydroxy‐ or cyanocobalamin. In most cases presented, at least weekly injections (1 mg IM) were necessary to ensure optimal treatment. Most centres adjusted the treatment regimen based on monitoring CBC, total plasma homocysteine, plasma and urine methylmalonic acid, as well as, clinical status. Finally, continuing IM treatment into adulthood appears to be beneficial.